Analisis Gender dalam Iklan Sunlight dan Deterjen Sayang di Televisi - Tirta Kencana; Nursapia Harahap (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Gender is the result of a social construct that is built, understood, and upheld within society. It arises from society's perceptions of the roles, behaviors, and identities of each individual's gender. The division of gender roles, behaviors, and identities can also stem from misunderstandings of societal paradigms. This study aims to analyze the role of gender in Sunlight and Sayang detergent advertisements on television. The research utilizes a qualitative method focusing on observation and understanding of social phenomena. This method includes detailed descriptive approaches to depict all aspects related to the research subject. Data collection instruments and techniques in this study employ documentary studies. Data analysis techniques utilize Ferdinand de Saussure's semiotics theory to search for signifier and signified. The results of this study indicate that the Sunlight advertisement portrays men and women as mutually supportive, no longer strictly adhering to gender roles constructed by social norms. Meanwhile, the Sayang detergent advertisement reinforces gender roles, particularly for women, depicting laundry as a woman's task. This is reinforced by its slogan, "Karena Ibu Perlu Dikasih Sayang," and the predominant pink color.